Islamic Higher Education in the ASEAN Region: From Opportunities and Challenges - Frank Dhont (Jurnal Pendidikan Islam, 2016)
This paper discusses the notion of Islamic Higher Education in ASEAN. It highlights the transformation of the ASEAN organization followed by the elaboration of Islamic Higher Education in the ASEAN Islamic Majority Nations of Brunei, Malaysia, and Indonesia. In these countries, some universities have emerged as exemplary institutions which are expected to uphold Islamic Higher Education. Opportunities and challenges of Islamic Higher Education among ASEAN countries are also discussed. Based on the investigation, it can be concluded that Islamic higher education has a proud tradition in Brunei, Indonesia and Malaysia and that now with the rising important of ASEAN there are ample opportunities for the development of IHE in ASEAN